1978
DOI: 10.1161/01.cir.57.3.440
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent sustained ventricular tachycardia. 2. Endocardial mapping.

Abstract: Endocardial ventricular mapping of 21 ventricular tachyardias (VT) in 17 patients was performed using electrode catheters. Activation at multiple left and right ventricular sites was utilized to determine the site of origin of the VT. Eleven VT had a left bundle branch block pattern (VT-LBBB) and 10 VT had right bundle branch block pattern (VT-RBBB). In all VT-RBBB the earliest site of activation was in the LV or septum. In VT-LBBB the earliest site was RV (4/11), LV (5/11) and septum (2/11). All ventricular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(76 citation statements)
references
References 22 publications
(2 reference statements)
3
73
0
Order By: Relevance
“…[1][2][3] Results of prior mapping studies indicated that reentrant VT in this setting often originate from the subendocardial surface of infarcted myocardium, adjacent to dense scar or aneurysm. [3][4][5] Nonischemic cardiomyopathy is characterized by myocardial dysfunction in the absence of significant coronary artery disease. In contrast to ischemic heart disease, little is known about the electrophysiological substrate for uniform VT in patients with nonischemic left ventricular (LV) cardiomyopathy.…”
mentioning
confidence: 99%
“…[1][2][3] Results of prior mapping studies indicated that reentrant VT in this setting often originate from the subendocardial surface of infarcted myocardium, adjacent to dense scar or aneurysm. [3][4][5] Nonischemic cardiomyopathy is characterized by myocardial dysfunction in the absence of significant coronary artery disease. In contrast to ischemic heart disease, little is known about the electrophysiological substrate for uniform VT in patients with nonischemic left ventricular (LV) cardiomyopathy.…”
mentioning
confidence: 99%
“…Early surgical treatments were performed in cases of major scars, so called ventricular aneurysms, which were resected (2,3) and within the same procedure, deep encircling incisions of different extent should isolate the electrically instable boarder zone from the remaining ventricle (4,5). With the introduction of electrophysiological investigations, the origin of such reentry circuits along the border zone was localized and an endocardial resection of this focus performed (6,7,8,9,10,11). However recurrent Vt´s were observed frequently after these procedures, oftentimes different from the primary clinical and also electrophysiological presentation.…”
Section: Surgical Treatment Optionsmentioning
confidence: 99%
“…The endocardial VT exit site was de ned as the site where the earliest endocardial breakthrough occurred relative to the onset of the QRS complex on the simultaneously recorded surface ECG. 19 An epicardial breakthrough was de ned as the absence of endocardial activity before or within 10 msec after the onset of the body surface QRS complex. If activation times of signals recorded at contiguous sites (7 to 9 mm apart) differed by 50 msec, conduction block was considered present.…”
Section: De Nitions Of Parameters and Related Terminologymentioning
confidence: 99%